PENGARUH BRAND IMAGE, BRAND AWERENESS DAN SERVICES QUALITY TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ACER PADA PT. BLOGGERKOMPUTER DI KECAMATAN MUARA BANGKAHULU KOTA BENGKULU - Saputra, Novherliyanto; Ratnawili, Ratnawili (Yayasan Insani Mandiri Santani, 2023)
Research at PT. Computer bloggers in Muara Bangkahulu District, Bengkulu City with the formulation of the problem How does Brand Image, Brand Awereness and Service Quality influence the Purchase Decision of Acer laptops at PT. Computer bloggers, population and sample in this study are all consumers at PT. Computer bloggers totaled 150 respondents. The sampling technique used convenience sampling based on predetermined criteria totaling 150 respondents. Observation data collection techniques, documentation and questionnaires. The processed data was analyzed using SPSS 24. Based on the results of research and analysis of the influence on Brand Image, Brand Awereness and service quality variables on Purchasing Decisions. the following conclusions can be drawn: Brand Image, Brand Awerenes, and Service Quality have a positive and significant effect partially on Acer laptop Purchase Decisions at PT Blogger Computer, and Brand Image, Brand Awerenes, and Service Quality, have a significant effect simultaneously on Purchase Decisions at Computer Blogger PT. Keywords: Brand Image, Brand Awareness, Quality of Service Purchase Decision